Exemplary Leadership in Higher Education: Study at Universitas Islam Syekh-Yusuf Tangerang - M. Rosul Asmawi; Seno Santoso; Muhamad Nur; Siti Maesaroh (International Journal of Social Service and Research (IJSSR), 2023)
This study aims to find out exemplary leadership: studies at Universitas Islam Syekh-Yusuf Tangerang. This research is very strategic, important and interesting, considering that exemplary leadership is very interesting to study in depth. For this reason, this research intends to take a more in-depth picture of exemplary leadership. Referring to the research focus, it can be understood that this research uses qualitative research with descriptive qualitative analysis, thus the data is presented descriptively, factually and systematically. this research shows that the Rector's leadership can still be drawn from exemplary behavior. The Rector's leadership can still be drawn from exemplary aspects, including aspects of (a) the intimacy of the Rector's leadership conversation is a little less focused; (b) the interactivity of the Rector's leadership is indeed less intense; (c) seen from the aspect of the Chancellor's leadership, the participation of the Chancellor appears to have a sense of responsibility for the dynamics that occur; and (d) this intentionality is indeed important, although it must be admitted that the Rector's activities are very numerous, and therefore cannot be monitored in detail. The Rector should have full time at work so that the dynamics can be observed carefully and the progress can be known clearly.